Application of Geogebra in Mathematics Learning Using a Realistic Mathematics Education Model - Al Ayyubi, Ibnu Imam; Rohaendi, Nendi; Prayetno, Eko; Nurhikmah; Masfuroh, Ai Sri; Raed Awadh Saeed Al-Ghatnaini; Tasnim Saelaemae (Journal of Teaching and Learning, 2025)
The application of GeoGebra in teaching still faces challenges such as teacher readiness and the availability of technology in schools, especially in mathematics learning. This research examines the correlation of the GeoGebra application to the mathematics learning outcomes of students whose learning uses the Realistic Mathematic Education learning model. This research was conducted at SDN 074 Ayudia, Bandung City using quantitative methods with a non-experimental approach. The population in this study were all students at SDN 074 Ayudia with a sample of 27 students in class VI B and the instruments used were questionnaires and tests. The sampling technique was carried out using a probability sampling technique based on cluster sampling. Meanwhile, the swimmer test from the data analysis carried out was a normality test using Kolmogorov-Smirnov assisted by the SPSS application. In this research, it can be concluded that there is no significant correlation between the application of Geogebra to the mathematics learning outcomes of students whose learning uses the Realistic Mathematic Education (RME) model, and the correlation is classified as very low. For further research, it is hoped that we can use other learning models to see the influence that occurs between the application of the Geogebra application in mathematics learning to see special equations in simple linear regression to be able to know the probability of the independent variable and the dependent variable.